2019
DOI: 10.1002/hyp.13393
|View full text |Cite
|
Sign up to set email alerts
|

The influence of groundwater representation on hydrological simulation and its assessment using satellite‐based water storage variation

Abstract: The interaction between surface water and groundwater is an important aspect of hydrological processes. Despite its importance, groundwater is not well represented in many land surface models. In this study, a groundwater module with consideration of surface water and groundwater dynamic interactions is incorporated into the distributed biosphere hydrological (DBH) model in the upstream of the Yellow River basin, China. Two numerical experiments are conducted using the DBH model: one with groundwater module ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
1
8
0
1
Order By: Relevance
“…Note that our approach is different from other previous studies. For instance, the developed approach by Niu et al (2007) and Huang et al (2019) extracts the baseflow from the aquifer, as a percentage of the storage or the water table depth using an exponential function. In our study, the flux of baseflow comes from the contribution of aquifer to the soil domain by an additional upward flux component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that our approach is different from other previous studies. For instance, the developed approach by Niu et al (2007) and Huang et al (2019) extracts the baseflow from the aquifer, as a percentage of the storage or the water table depth using an exponential function. In our study, the flux of baseflow comes from the contribution of aquifer to the soil domain by an additional upward flux component.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main classifications of groundwater coupling, namely, the empirical lumped GW models and the physically based distributed GW models (Tian et al, 2012). Regarding their dimension, this can be either a one‐dimensional (1‐D) model (e.g., Gedney & Cox, 2003; Maxwell & Miller, 2005; Yeh and Eltahir, 2005a; Niu et al, 2007; Huang et al, 2019), two‐dimensional (2‐D) model (e.g., Fan & Miguez‐Macho, 2011; Vergnes & Decharme, 2012) or 3‐D model (e.g., Gutowski Jr et al, 2002; Maxwell et al, 2011; Tian et al, 2012; York et al, 2002). In the 1‐D coupling, the soil domain is extrapolated for a few tens of meters.…”
Section: Introductionmentioning
confidence: 99%
“…The groundwater model developed for this study can correctly capture these characteristic differences of groundwater and baseflow. Similarly, Huang et al (2019) showed that the use of a groundwater layer in a hydrological model can improve simulated surface discharge, particularly during low flows when baseflow contribution is high. A large-scale model including lateral flows offers the opportunity to disentangle both the diversity of groundwater responses and the differences of groundwater head and baseflow fluctuations, that is, the difference of groundwater drought and the groundwater's role in drought propagation.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…冰川融水径流除了对下游河流、湖泊等水体径流 和水位产生影响之外, 也可能增加土壤含水量、补给 壤中流等影响地表产流过程, 从而改变下游河道径流, 这一影响过程往往更具有长期性 [67] . 黄河源区径流受 冰川融水影响较大, 但汛期则以降水为主, 因此源区出 口(唐乃亥站)汛期径流减少与源区降水减少导致的径 流变化有较大关系 [68] ; 枯季地下水是径流的重要补给 来源, 枯季径流的年际变化可能与冰雪融水有较大关 系 [69] . 雅鲁藏布江从上游到下游受地下水补给和融水 补给的比例逐渐增大, 近年来在全球变暖导致冰川退 缩加剧的背景下, 上游融水径流变化对下游的影响可 能更为显著和深刻 [67] .…”
Section: 流域冰川径流对气候变化的响应 结果显示 目前45%unclassified